Preliminary Comparative Analysis of Phenological Varieties of Quercus robur by ISSR-Markers. (22nd February 2016) - Chokheli, Vasiliy; Kozlovsky, Boris; Sereda, Mikhail; Lysenko, Vladimir; Fesenko, Igor; Varduny, Tatiana; Kapralova, Olga; Bondarenko, Elena
Abstract : Quercus robur L. is a valuable wood species having long ontogeny and promising to create long-living artificial plantings of recreational and ameliorative purposes in the steppes zone of Russia and other countries. In this work we have performed the genotyping of varieties of Quercus robur L. obtained from collection of Botanical Garden of Southern Federal University using intersimple sequence repeat (ISSR) molecular markers. The most polymorphic ISSR-marker (GA) 8YC was found in the collection. The polymorphic DNA markers identified in the present study can be used for the future breeding works to obtain valuable genotypes of Quercus genus. In addition we have performed DNA fingerprinting of the prospective sample of the variety Q. robur var. tardiflora Czern.